Rapid Assessment of Third Round of Sub PIN Diphteria at Tambakrejo Village Jombang - Fatikhatul Ummamah (Jurnal Berkala Epidemiologi, 2016)
In the third round Sub-National Immunization Week (Sub-PIN) Diphtheria in Tambakrejo Village, Jombang District has a low coverage value and does not meet the target (95%) at the age of 2-36 months (61.77%) and ages 3-7 years (82.39%). This study aims to describe more deeply about the implementation of the third round diphtheria Sub-PIN in November 2013. This research is a descriptive study with a cross-sectional study design. The population of this study was all parents who had children aged 2 months - 15 years at the time of the implementation of the third round of diphtheria sub-PIN in Tambakrejo Village. The sample in this study were 150 people taken using cluster random sampling. Variables in this study include the status of immunization of children with sub-PIN, reasons for not participating in sub-PIN, the source of information on sub-PIN, characteristics of respondents including age, level of education, occupation, number of children, knowledge, and age of children. The results of this study indicate that as many as 26% of respondents did not include their children in diphtheria sub-PIN with the majority of reasons being children who did not want or cry (56.4%). Respondents who did not include their children in the third round diphtheria sub-PIN have received information (92.3%), are over 30 years old (66.7%), have high school education (61.5%), do not work (66.7%), have ≤ 2 children (61.5%), have a high level of knowledge (76.9%), have children between the ages of 2–36 months (43.6%) and 7-15 years (43.6%). Health workers need to do counseling and personal approach, especially for parents whose children refuse to be immunized regarding the benefits of Sub PIN.